MAKNA HIDUP DALAM KASIH MENURUT RASUL PAULUS BERDASARKAN ROMA 12:9-21 - Estherlina Maria Ayawaila (Sekolah Tinggi Teologi Arastamar Bengkulu, 2017)
Romans are letters written by the Apostle Paul addressed to the church in Rome. One of the purposes of this letter is that in conveying love you have the correct method so that love can be done. The duty of believers is to convey love to those who have not done love like the Lord Jesus did. Problems to love can arise from a lack of understanding about love, understanding but not doing or starting to degrade the meaning of love in believers. Therefore this paper tries to remind again about the warmth of love for believers. In writing this scientific work the writer will explore how the meaning of life in love according to the Apostle Paul based on Romans 12: 9-21. To deepen the study of the writer uses the writing method which looks at the meaning of the right life in doing love especially in Romans 12: 9-21. So that this scientific work is easy to understand at the end, write a practical application in loving.